The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1158/0008-5472.can-14-1778
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Pharmacological Inactivation of the Purinergic P2RX7 Receptor Dampens Inflammation but Increases Tumor Incidence in a Mouse Model of Colitis-Associated Cancer

Abstract: Colitis-associated cancer (CAC) is a complication of inflammatory bowel disease (IBD). Binding of extracellular ATP to the purinergic receptor P2RX7 has emerged as a critical event in controlling intestinal inflammation, acting to limit elevation of proinflammatory mast cells and cytokines and promote survival of regulatory T cells (Treg) and enteric neurons. In this study, we investigated the effect of P2RX7 blockade in an established mouse model of CAC. Using genetic and pharmacologic tools, we found unexpec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
103
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(115 citation statements)
references
References 49 publications
5
103
1
6
Order By: Relevance
“…Understanding the complex and sequential molecular mechanisms by which macrophages are recruited to the intestines in response to bacteria remains an important goal to treat gut-origin sepsis. Additionally, the administration of P2X7R inhibitors suggests caution given the possibility of increasing the risk of tumor growth 41, 42 . The present study did not investigate the possible effects of P2X7R on the proliferation of IECs.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the complex and sequential molecular mechanisms by which macrophages are recruited to the intestines in response to bacteria remains an important goal to treat gut-origin sepsis. Additionally, the administration of P2X7R inhibitors suggests caution given the possibility of increasing the risk of tumor growth 41, 42 . The present study did not investigate the possible effects of P2X7R on the proliferation of IECs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the complete picture is probably more complicated and could be dependent upon the kind of malignancy analyzed. Purinergic receptors like P2×7R have been shown to promote cancer growth and progression in certain conditions [21, 33] while, in some case, to partially prevent cancer growth by immune infiltration [34, 35]. …”
Section: Discussionmentioning
confidence: 99%
“…This suggests that there is a relationship between the P2X7 receptor sensitivity and the ability of these mice to respond to and eliminate intracellular pathogens because WT C57BL/6 J mice have a proline to leucine polymorphism at amino acid 451 in the C-terminal tail of the P2X7 receptor, which reduces the P2X7 sensitivity to ATP [28]. In murine model of colitis, P2X7-deficient mice showed reduced tissue damage in the colon [29] and faster recovery from epithelial damage caused by an inducing agent [30]. Nevertheless, we observed that the absence of the P2X7 receptor during in vivo infection caused by L. amazonensis resulted in more severe injury in mice.…”
Section: Discussionmentioning
confidence: 99%